Educação, ensino e literatura : a trajetória da professora Maria da Conceição Ouro Reis no Colégio de Aplicação da Universidade Federal de Sergipe (1973-1991) - Santos, Alfredo Bezerra dos (2022)
This research presents historiographical understandings on the trajectory of the teacher Maria da Conceição Ouro Reis (1973 -1991), emphasizing her literary production and its relation to her teaching practice at the Laboratory School of the Federal University of Sergipe (UFS). The school, in this context, will be recognized both as the place of her experiences and as the environment where her teaching actions had greater projection, although there are records of her teaching participation in more than one educational institution, such as the Catholic Faculty of Philosophy of Sergipe, Atheneu Sergipense College, and private schools. This research defends the hypothesis that the use of literature as a resource to encourage students’ creation and writing practices marks the didactic activities of the teacher Conceição Ouro Reis at the Laboratory School. The study sought to understand aspects of the teaching practice of Professor Conceição Ouro at the Laboratory School at UFS. In this sense, the following steps were prioritized as specific objectives: a) To analyze aspects of the teacher's training and teaching activity; b) To identify her literary production and its relation to her teaching practices; c) To examine literary projects she developed in the institution; d) To investigate the literary influence in her students’ writing processes. The inquiry considers ideas from cultural history, debating the history of teacher education from a specific reference point (narrative of trajectory in the teaching profession), with the contribution of oral history. Sources underlying this work include proceedings book, textbooks, newspapers, the teacher's personal collection, along with her literary and pedagogical production, among others. Document gathering was carried out in the archive of the Center for Research, Documentation, and Memory of the Laboratory School (CEMDAP), as well as in digital and personal collections. In addition to written sources, the methodology of Oral History was used, oral reports were used. They were collected through interviews with former students of Conceição Ouro, ex-teacher colleagues, and publishing colleagues. The choice for those individuals is based on the understanding that they mark relationships of dialogue, work, and experiences both at school and in society, thus representing the teacher's circulation through different spaces. As a result, it is evident that, in her initiative, the teacher interferes in the education framework in several ways, namely: the implementation of the discipline of Literature in the Laboratory School; the development of Portuguese study projects; the encouragement of literary habits, leading students to authorial gestures. Therefore, the research confirms the assumption/hypothesis that the use of literature encouraged students' writing practices.